Ultrastructure of Arteries after Devitalization with Low Temperatures and Ionizing Irradiation - Byzov, D. V.; Repin, N. V.; Marchenko, L. N.; Govorukha, T. P.; Mikhaylova, I. P.; Synchykova, O. P.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2011)
The report represents the data of electron microscopic study of small-diameter arteries following cryotreatment and ionizing irradiation. Combination of freeze-thawing with following irradiation by electron beam was shown to result in a complete devitalization of arteries while maintaining the connective-tissue frame intact.